ANDROID-BASED OUTPATIENT REGISTRATION SYSTEM DESIGN AT KARANG PULE PUBLIC HEALTH CENTER - Musparlin Halid; Ikhwan; Wulandari Dewi Susilawati (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
Karang Pule Public Health Center (PHC) in Mataram, the patient or the patient's family registers by coming directly to the puskesmas. This system causes patients or their families have to wait a long time and the danger is they are vulnerable to Covid-19 transmission. Another impact is frequent errors in the selection of the queue place. Queue place is divided into 2 parts, namely queue A and queue B. Queue A is for patients under 55 years old and queue B is for elderly people above 55 years. Some patients, especially the elderly who do not know their age, cause patients to choose the wrong place to queue and wait even longer. The research objective is to design an Android-based outpatient registration system. The methodology used in this design the application is Waterfall. Data collection techniques used such as observation, interviews, and literature studies. This research produced an application design where patients can see the queue number being served so that patients can estimate the time to come to the intended polyclinic.